Economic Path Scheduling for Mobile Agent System on Computer Network (Springer Link, 2023)
Mobile agent technology has a lot of gains to offer network-centric applications. The technology promises to be very suitable for narrow-bandwidth networks by reducing network latency and allowing transparent per-to-per computing. Multi-agent technology had been proposed for many network-centric applications with little or no path scheduling algorithms. This paper describes the need for path scheduling algorithms for agents in multi-agent systems. Traveling salesman problem (TSP) scheme is used to model ordered agents and the unordered agents schedule their path based on random distribution. The two types of agents were modeled and simulated based on bandwidth usage and response time as performance metrics. Our simulation results shows that ordered agents have superior performance against unordered agents. The ordered agents exhibit lower bandwidth usage and higher response time. KeywordsTSP-Ordered Agent-Bandwidth Usage-Response time-Routing model.